Overall calibration method of multibeam echo sounder installation biases based on terrain feature matching - LI Tie (Acta Geodaetica et Cartographica Sinica, 2019)
The patch test method based on decoupling principle to determine MBES (multibeam echo sounders)installation biases often results in complex operation and low accuracy due to theoretical imperfections. Therefore, the overall calibration of the biases is proposed. Firstly, MBES sounding terrain is converted into grayscale image. Then, SIFT(scale-invariant feature transform) is used for matching related terrain images and founding matching point pairs. Finally, the inequality-constrained least square adjustment is used for obtaining the MBES installation biases by the matching point pairs coordinates. The experiment verifies the validation of this method in simplifying the implementation and improving the accuracy of determining these biases.